(untitled) (Bangladesh Journal of Medical Science, 2025)
Dental students often face high academic workloads, clinical demands, and performance pressures, which can lead to significant psychological stress. Understanding research trends in this area can guide strategies to protect student wellbeing. This study examined the global research landscape on the mental health of dental students, focusing on the most cited studies published between 2000 and August 2025. The bibliometric analysis was conducted using the Dimensions database. The search included terms related to mental health, stress, anxiety, depression, and burnout in dental students. Out of 1403 articles obtained after applying a filter for publication type and time, the 500 most cited articles were screened manually, and 367 met the inclusion criteria. Data were analyzed using Biblioshiny to identify publication trends, geographical distribution, influential journals, most cited articles, and thematic evolution. Research output increased steadily over the years, peaking in 2021, followed by a decline. Saudi Arabia, India, and the United States produced the largest share of highly cited studies. The Journal of Dental Education was the most frequent publishing journal. Thematic evolution showed a shift from early focus on attitudes and academic environment to more recent emphasis on burnout, psychological stress, and measurable health impacts such as bruxism and reduced quality of life. COVID-19–related mental health issues were a major theme between 2019 and 2020. Most highly cited studies were cross-sectional surveys, with recent years showing more review articles. The findings highlight the need for more intervention-based, longitudinal, and multicenter studies to support evidence-based mental health strategies for dental students worldwide. BJMS, Vol. 24 No. 04 October’25 Page : 1050-1061